1064 nm SERS of NIR active hollow gold nanotags. Issue 3 (5th December 2014) - Kearns, H.; Shand, N. C.; Smith, W. E.; Faulds, K.; Graham, D.
Abstract : NIR active hollow gold nanotags have been developed to provide effective SERS when excited at 1064 nm. Abstract : Surface enhanced Raman scattering (SERS) tags are in situ probes that can provide sensitive and selective probes for optical analysis in biological materials. Engineering tags for use in the near infrared (NIR) region is of particular interest since there is an uncongested spectral window for optical analysis due to the low background absorption and scattering from many molecules. An improved synthesis has resulted in the formation of hollow gold nanoshells (HGNs) with a localised surface plasmon resonance (LSPR) between 800 and 900 nm which provide effective SERS when excited at 1064 nm. Seven Raman reporters containing aromatic amine or thiol attachment groups were investigated. All were effective but 1, 2-bis(4-pyridyl)ethylene (BPE) and 4, 4-azopyridine (AZPY) provided the largest enhancement. At approximately monolayer coverage, these two reporters appear to pack with the main axis of the molecule perpendicular or nearly perpendicular to the surface giving strong SERS and thus providing effective 1064 nm gold SERS nanotags.